Sikap, norma subjektif dan persepsi mengamalkan adab belajar dalam pelaksanaan latihan hijrah pelajar sekolah berasrama penuh - Harun, Norlia (2017)
Fully Residential Schools (SBP) are well known for their high achieversand brilliant students; nonetheless, there are also SBP students who are lowachievers due to their negative attitude, subjective norms and perceptual controltowards learning practices. This case study was conducted to evaluate thesuitability of Latihan Hijrah in helping low achievers improve theirunderstanding, attitude, subjective norms and perceptual control towardsachieving a more positive learning practice. This study involved six SBP lowachieving students who were selected using purposive sampling. The studentsneeded to undergo Latihan Hijrah in a form of group guidance before data werecollected through interview, observation forms and Learning PracticeQuestionnaire. The findings of the interview show that the students experiencedpositive changes in terms of understanding, attitude, subjective norms,perceptual behavioural control and behaviours towards learning practices afterthey underwent Latihan Hijrah. This behavioural changes are also seen throughobservation results. These findings are supported by pre and post test resultsusing the Learning Practice Questionnaires which show an increased score afterthe students followed Latihan Hijrah. Hence, this finding proved that LatihanHijrah is suitable to be used in helping low achievers students improve theirunderstanding, attitude, subjective norms, perceptual and behavioural control forlearning practices. Latihan Hijrah is expected to be fully conducted in all SBPsto help low achievers to change their attitude, subjective norms, and perceptualcontrol for learning practices towards excellent achievements.